High-current density alkaline electrolyzers: The role of Nafion binder content in the catalyst coatings and techno-economic analysis - Zappia, Marilena Isabella; Bellani, Sebastiano; Zuo, Yong; Ferri, Michele; Drago, Filippo; Manna, Liberato; Bonaccorso, Francesco (Frontiers in Chemistry, 2022)
We report high-current density operating alkaline (water) electrolyzers (AELs) based on platinum on Vulcan (Pt/C) cathodes and stainless-steel anodes. By optimizing the binder (Nafion ionomer) and Pt mass loading (mPt) content in the catalysts coating at the cathode side, the AEL can operate at the following (current density, voltage, energy efficiency -based on the hydrogen higher heating value-) conditions (1.0 A cm−2, 1.68 V, 87.8%) (2.0 A cm−2, 1.85 V, 79.9%) (7.0 A cm−2, 2.38 V, 62.3%). The optimal amount of binder content (25 wt%) also ensures stable AEL performances, as proved through dedicated intermittent (ON-OFF) accelerated stress tests and continuous operation at 1 A cm−2, for which a nearly zero average voltage increase rate was measured over 335 h. The designed AELs can therefore reach proton-exchange membrane electrolyzer-like performance, without relying on the use of scarce anode catalysts, namely, iridium. Contrary to common opinions, our preliminary techno-economic analysis shows that the Pt/C cathode-enabled high-current density operation of single cell AELs can also reduce substantially the impact of capital expenditures (CAPEX) on the overall cost of the green hydrogen, leading CAPEX to operating expenses (OPEX) cost ratio <10% for single cell current densities ≥0.8 A cm−2. Thus, we estimate a hydrogen production cost as low as 2.06 kgH2−1 for a 30 years-lifetime 1 MW-scale AEL plant using Pt/C cathodes with mPt of 150 μg cm−2 and operating at single cell current densities of 0.6–0.8 A cm−2. Thus, Pt/C cathodes enable the realization of AELs that can efficiently operate at high current densities, leading to low OPEX while even benefiting the CAPEX due to their superior plant compactness compared to traditional AELs.